Exploring self-regulated learning support for AI related work in an insurance firm - Mohd Rasdi, Roziah; Umar Baki, Nordahlia; Mohd Rasdi, Roslina (IEEE, 2023)
Self-regulated learning needs to be enhanced and supported for the sustainability of e-learning and skill development particularly in the context of workplace implementing artificial intelligence (AI). This study explores the support mechanism for SRL experienced by insurance agents in an insurance firm adopting AI technologies. The case study involves seven participants who were purposively selected based on the criteria of the study. Data were analysed using thematic analysis, and then triangulated and checked by members for trustworthiness and credibility. The themes that emerged are (i) training and development for agent; (ii) self-learning initiatives; (iii) knowledge sharing; and (iv) adaptation to change. To conclude, SRL practices require strong support from organisation in order to provide stimulating learning environment. In addition, individual agency would empower SRL and make learning more engaging and effective.